Hubungan Individu, Konsep dan Kepentingan kepada Dakwah Islam - Hj. Syed Hussin, Syed Abdurahman (Jurnal Usuluddin, 1995)
The article tries to portray the manner of individual interaction in a Muslim community and the importance of strategy of action of an Islamic movement.